Molecular and bioacoustic differentiation of Boophis occidentalis with description of a new treefrog from north-western Madagascar - Vences, Miguel; Andreone, Franco; Glos, Julian; Glaw, Frank (Zootaxa, 2010)
We describe a new species of the Boophis albilabris group (Anura: Mantellidae) from north-western Madagascar. Boophis tsilomaro sp. nov. is most similar to B. occidentalis from the Isalo Massif, but differs by substantial genetic differentiation, larger size, absence of a turquoise iris colour, presence of a more distinct white stripe along upper lip in life, and longer note duration and lower pulse repetition rate in advertisement calls. Due to its small known range and continuing decline in the extent and quality of its habitat we propose to classify this new species as "Critically Endangered" according to the IUCN criteria. We also describe the advertisement calls of B. occidentalis for the first time.